EP985 Morbidity outcomes of cytoreductive surgery in advanced low grade serous and sex chord stromal tumor. (1st November 2019) - Shylasree, T; Dash, B; Bhandare, M; Bansal, R; Ghosh, J; Mahajan, D; Kerkar, R; Maheshwari, A
Abstract : Introduction/Background: Extensive Cytoreductive surgery (CRS) is the main stay of treatment for advanced Low grade serous ovarian cancer(LGSC) and sex chord tumor (SCST) group, however due to young age at presentation and good performance status, major surgical complications are lower than serous high grade tumors(HGSC). Aim: To assess Postoperative morbidity of CRS in advanced LGSC/SCST. Methodology: Nineteen patients with extensive abdominal disease underwent CRS from June 2016–Jan 2019. The median age was 43 yrs (22–56). 15 patients had LGSC and 4 patients had SCST confirmed on histology. Ten out of 19 patients had received chemotherapy with no response prior to referral. Results: Mean PCI was 15(6–30). Fifteen patients had complete cytoreduction (CC-0/1). The median surgical time was 9 hrs. (2.5–10.5). Seventeen patients underwent peritonectomy, 10 patients needed multiple GI resections, 1 patient distal pancreaticosplenectomy, 1 patient had an elective nephrectomy for nonfunctioning kidney. Median blood loss was 2500 ml (250–11500 ml). Median postoperative ventilation required was 1 day (0–7), Median ICU stay 3 days (1–10) and hospital stay 16 days (9–38). Seventeen patients had minor postoperative complication. Three had grade 3–4 complication (aortic graft, wound dehiscence, SIRS with prolonged intubation). There was no postoperative mortality. Median follow up was 14 months (3–30). LGSC patients were put on either letrozole /tamoxifen as maintenance therapy. Nine patients are disease free, 6 have stable disease and 3 have progressive disease, one lost to follow up. Overall median PFS is 14 months. The average cost of treatment was USD 1542 and USD 13878 for subsidized/nonsubsidized category respectively. Conclusion: CRS in LGSC/SCST has lower morbidity and almost nil mortality compared to published literature in HGSC. This may be attributable to younger age and good performance status of such patients. However the cost of surgery needs to be addressed in mid-income countries. Disclosure: Nothing to disclose.